Implicações da relação entre docentes e intérpretes de libras na educação profissional técnica de nível médio (EPTNM) - Feitoza, Adriano Brito (2024)
The teacher and the Libra interpreter translator must be aware of their roles in the inclusion of deaf students by using educational practices. In this way, the relationship between teacher and Libra interpreter translator will bring positive implications that benefit deaf students in the classroom. And as a consequence, it allows deaf students to cross their learning trajectory that occurs in Secondary Technological Professional Education (EPTNM) towards Polytechnic education, one of the conceptual bases of EPTNM. The general objective is to summarize which educational practices can be implemented in the relationship between teacher and Libras interpreter in the classroom. The data collection instruments correspond to interviews and questionnaires aimed at the research objects, then ATD (Discursive Textual Analysis) was used as an methodology to collect the data. The results translate into educational practices that correspond to expertise developed by Libras teachers and interpreters that favor the work of these professionals to include deaf students in the classroom. As feedback from this research as linked to the objectives of PROFEPT (Postgraduate Program in Professional and Technological Education), an Educational Product (EP) was prepared with recommendations for educational practices for teachers and translators who interpret Libras.